Katharine Amend Kellock papers - Kellock, Katharine Amend, 1892-; Kellock, Harold, 1879-1953.
Correspondence, writings, project reports, printed matter, and other papers relating chiefly to Kellock's work with the Federal Writers' Project where Kellock worked as editor of the American Guide Series. Includes material concerning her work with the U.S. Resettlement Administration and at the U.S. Dept. of State where she focused on German affairs, a biography of John Adams, the Council of Foreign Ministers, her dealings with the U.S. Congress House Committee on Un-American Activities (Dies Committee), and investigations by the U.S. Civil Service Commission and the U.S. Federal Bureau of Investigation. Also includes papers of Harold Kellock pertaining to Harry Houdini and Sir Arthur Conan Doyle. Correspondents include Van Wyck Brooks and Bernard Augustine De Voto.
Library of Congress Prints and Photographs Division.
Economist and editor.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Adams, John, -- 1735-1826.; Brooks, Van Wyck, -- 1886-1963 -- Correspondence; De Voto, Bernard Augustine, -- 1897-1955 -- Correspondence; Doyle, Arthur Conan, -- 1859-1930.; Houdini, Harry, -- 1874-1926.; United States. -- Congress. -- House. -- Committee on Un-American Activities; United States Civil Service Commission; United States. -- Department of State; United States. -- Federal Bureau of Investigation; United States. -- Resettlement Administration; Council of Foreign Ministers; Federal Writers' Project; American guide series; Germany -- Foreign relations -- United States; United States -- Foreign relations -- Germany; Economists; Editors